A documentação como ferramenta de preservação: protocolos para documentação e gestão do acervo artístico da UFMG - Ana Martins Panisset (2017)
This PhD research aims to reaffirm and emphasize the relevance of documentation processes and their integrated management as indispensable tools for procedures in collection preservation. To this end, it presents protocols for preservation policies, documentation and management of the UFMG´s Artistic Collection. The collection constituted along the UFMG´ trajectory, currently has approximately 1500 objects such as paintings and religious sculptures from the 16th to the centuries, paintings and watercolors of 19th and 20th century landscapes; portrait of UFMG teachers; mural paintings; studies for panels; sculptures; engravings; photographs; and books of artists produced in the 20th and 21st centuries.In order to problematize the insertion and the formation of collections in the universities, it was necessary to discuss aspects that involve the history and the unfolding of actions that anticipate the recognition, the management, the safeguard and the necessity of articulation in the local, national and international scopes. Such collections, although accumulated within the university, are often not formed in the trajectory of research and teaching activities. Faced with such challenges, this research aims to establish subsidies for the discussion of the need for documentation for knowledge and visibility of university collections, in the case, especially the collections of art. The recognition of this important patrimony brings to the fore need to establish management policies in the university context and an effective commitment of the management bodies in the preservation of these collections, with a view to their integration into university actions of teaching, research and extension.Faced with the challenges of the relationship between theory and practice in matters related to documentation in museums, it is hoped that this thesis will contribute to the deepening of knowledge about the subject. In the same direction, it is also intended that this research collaborate with the approximation between the areas of Conservation, Museology, Information Science and Documentation.